Avaliação de pimenta biquinho com uso de adubo mineral e biofertilizante: produção, variáveis dimensionais do fruto e análise físico-química - Pereira, José Maurício (Universidade Federal de São Carlos, 2019)
The species of peppers that belong to the Capsicum genus are worldwide cultivated and the Biquinho type (C. chinense) has been gaining prominence in the national scenario due to its sweet taste and absence of pungency. The aim of this study is to search for an alternative fertilizer to produce this kind of pepper and to evaluate the agronomic characteristics of production, the fruit dimension and physical-chemical analysis. It was used a randomized design block with four replicates (four blocks) and three treatments: T1 – mineral fertilizer, T2 – biofertilizer and T3 – control, totalizing 12 plots. The research lasted 231 days, and nine fruit harvest were made. The following variables of production per plant were evaluated: number and mass of fruits (g/plant). Regarding the dimensional parameters of the fruit: wall thickness, diameter, fruit mass and length. For the physical-chemical analysis were evaluated: chlorophyll; humidity; titratable acidity; soluble solids; pH; firmness and ascorbic acid. For the production parameters (weight and mass of the fruits), the treatment with liquid biofertilizer application was superior than the other treatments. About the dimensional variables of the fruit (length, diameter, mass and wall thickness) there was no significant different between treatments with liquid biofertilizer and mineral fertilizer, however, the control treatment presented inferior results. In the physical-chemical analysis, the control treatment presented a lower content of chlorophyll and the peppers produced with chemical fertilizer showed higher levels of acidity, also as control, and lower pH. There was no significant difference between the treatments regarding the levels of humidity, soluble solids, firmness and ascorbic acid. In front of the results, the liquid biofertilizer proved to be a satisfactory alternative to produce this kind of pepper.
Evaluation of biquinho pepper with mineral fertilizer and biofertilizer: production, dimensional fruit variables and physical-chemical analysis
Keywords: Avaliação agronômica; Agroecologia; Produtividade; Capsicum chinense; Composição química; Agronomic evaluation; Agroecology; Productivity; Chemical composition; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO::FERTILIDADE DO SOLO E ADUBACAO; CIENCIAS AGRARIAS